2010
DOI: 10.1007/s10549-009-0709-2
|View full text |Cite
|
Sign up to set email alerts
|

Variants in DNA double-strand break repair genes and risk of familial breast cancer in a South American population

Abstract: The double-strand break (DSB) DNA repair pathway has been implicated in breast cancer (BC). RAD51 and its paralogs XRCC3 and RAD51D play an important role in the repair of DSB through homologous recombination (HR). Some polymorphisms including XRCC3-Thr241Met, RAD51-135G>C, and RAD51D-E233G have been found to confer increased BC susceptibility. In order to detect novel mutations that may contribute to BC susceptibility, 150 patients belonging to 150 Chilean BRCA1/2-negative families were screened for mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…The Thr241Met substitution is the most thoroughly investigated polymorphism in XRCC3 due to the C>T transition at exon 7. Functional data also suggest that the polymorphism may be associated with slightly decreased DNA repair capacity (Jara et al, 2010). Kiuru et al (2008) studied the XRCC3 Thr241Met polymorphism in samples of nervous system tumors and concluded that the genotype Thr/Met and homozygous Met/Met are associated with increased risk for developing this kind of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The Thr241Met substitution is the most thoroughly investigated polymorphism in XRCC3 due to the C>T transition at exon 7. Functional data also suggest that the polymorphism may be associated with slightly decreased DNA repair capacity (Jara et al, 2010). Kiuru et al (2008) studied the XRCC3 Thr241Met polymorphism in samples of nervous system tumors and concluded that the genotype Thr/Met and homozygous Met/Met are associated with increased risk for developing this kind of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies in different populations should be compared to justify this thesis (Brooks et al 2008;Jara et al 2010;Wang et al 2010;Gao et al 2011). Brooks et al (2008) showed that ethnicity was significantly associated with breast cancer risk and the genotype of RAD51 gene.…”
Section: Discussionmentioning
confidence: 99%
“…BRCT domains are also found in other breast-cancerrelated genes such as XRCC4 or FANCG. It is normative for these gene products to form protein complexes that can mediate repair of DNA damage [10,64,65] . Mutations in the BRCT domain of BRCA1 which inactivate its binding capacity, can result in increased single stranded DNA and hyper-recombination rates without changes to nonhomologous end-joining DNA repair mechanisms [30] .…”
Section: Defects In Dna Repair Pathways Associated With Breast Cancermentioning
confidence: 99%
“…The genes involved in heritable susceptibility to cancer often function as DNA damage response effectors or cell cycle control effectors [4,9] . Inherited breast cancers occur early and in pre-menopausal years because of the increased risk of loss of heterozygosity, and thus loss of gene expression of a DNA damage response or cell cycle control effector gene product [6,10] . Only 5%-10% of breast cancer cases are thought to be caused by germ-line mutation [5,8,11] .…”
Section: Introductionmentioning
confidence: 99%